Study of bioethics scientific production in Spanish on people with disabilities from journals indexed in Scopus - Pezo-Jimenez, Omar (2024)
The analysis of scientific production in bioethics related to disability reveals a panorama in which the transition to digital scientific journals has facilitated access to knowledge in Latin America, supported by public policies and principles of openness. However, there is a disparity in the quantity and diversity of studies with a predominance of the English language and a significant concentration in Spain. This highlights the need for greater diversity and equity in scientific production, especially in Latin America. Research addresses a variety of crucial issues, from mental health to access to education and labor inclusion, but faces challenges such as the scarcity of studies in languages ​​other than English and the lack of attention to realities other than the English-speaking one. In conclusion, there is within the reality of scientific research, a predominance of publications in English and a notable concentration of studies in Spain, which underlines the urgent need for greater diversity and equity within Latin American scientific production.